2023
DOI: 10.3390/molecules28031250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Winemaking on Phenolic Compounds and Antioxidant Activities of Msalais Wine

Abstract: Msalais wine (MW) is a popular traditional wine with the cultural characteristics of a specific Chinese ethnic group. In this study, phenolic profiles and antioxidant characteristics were identified using chromatographic analysis. A total of thirty-eight compounds, including eight furans, eleven phenolic acids, fourteen flavonoids, and five others, were identified via LC-MS/QTOF. It was found that catechin is the most abundant phenolic compound in MW, followed by epicatechin, gallic acid, caffeic acid, rutin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Phenolic compounds (such as flavonoids, phenolic acids and tannins) were the most abundant secondary metabolites in the samples of fermented grains Chetrariu and Dabija (2021) . It has been reported that phenolic compounds have a considerable impact on the overall sensory quality of finished baijiu, such as the quality and taste ( Hou, Chen, Pu, et al, 2023 ). In order to reveal the changes of phenolic metabolites of fermented grains at different fermentation stages, it was necessary to screen out phenolic metabolites and analyze them emphatically.…”
Section: Results and Analysismentioning
confidence: 99%
“…Phenolic compounds (such as flavonoids, phenolic acids and tannins) were the most abundant secondary metabolites in the samples of fermented grains Chetrariu and Dabija (2021) . It has been reported that phenolic compounds have a considerable impact on the overall sensory quality of finished baijiu, such as the quality and taste ( Hou, Chen, Pu, et al, 2023 ). In order to reveal the changes of phenolic metabolites of fermented grains at different fermentation stages, it was necessary to screen out phenolic metabolites and analyze them emphatically.…”
Section: Results and Analysismentioning
confidence: 99%
“…In the context of wine production, fermentation conditions take precedence. Factors such as the maceration period, whether the fermentation is spontaneous or involves the addition of specific yeasts and/or enzymes, and the fermentation temperature should all be considered (Hou et al., 2023; Lisov et al., 2023; Ntuli et al., 2023). It has been estimated that factors like maceration time and the addition of additives such as SO 2 , pectolytic enzymes, and enological additives, significantly influence the final content of polyphenols (Atanacković et al., 2012).…”
Section: Phenolic Compounds: From Grape To Winementioning
confidence: 99%
“…A set of six specific phenolic compounds were selected to evaluate the effects of the processing techniques. These compounds were selected based on their relationships with the oxidation processes in white wines and also in order to represent different phenolic families (benzoic acids, cinnamic acids, and flavanols) that are related to specific parts of grapes, i.e., grape pulp, skin, and seeds [23,24].…”
Section: Characterization Of Individual Phenolic Compounds In Wines W...mentioning
confidence: 99%